2007
DOI: 10.1103/physrevlett.98.066801
|View full text |Cite
|
Sign up to set email alerts
|

Electron Bunching in Transport through Quantum Dots in a High Magnetic Field

Abstract: Shot noise measurements provide information on particle charge and its correlations. We report on shot noise measurements in a generic quantum dot under a quantized magnetic field. The measured noise at the peaks of a sequence of conductance resonances was some 9 times higher than expected, suggesting bunching of electrons as they traverse through the dot. This enhancement might be mediated by an additional level, weakly coupled to the leads or an excited state. Note that in the absence of a magnetic filed no … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 28 publications
3
37
0
Order By: Relevance
“…Examples of such systems are quantum dots that are coupled to ferromagnetic leads [7][8][9][10] , multi-levels quantum dots 11,12 , multidots structures [13][14][15][16][17][18] , and also three terminal quantum dots [19][20][21] . There are also experimental works [22][23][24][25][26] in which a super-Poisson noise was measured in quantum dots, rather than the sub-Poisson noise, which is expected from the single level model of the quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such systems are quantum dots that are coupled to ferromagnetic leads [7][8][9][10] , multi-levels quantum dots 11,12 , multidots structures [13][14][15][16][17][18] , and also three terminal quantum dots [19][20][21] . There are also experimental works [22][23][24][25][26] in which a super-Poisson noise was measured in quantum dots, rather than the sub-Poisson noise, which is expected from the single level model of the quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the bunching of tunneling events, observable as an increased shot noise power, can characterize the Coulomb interaction in the transport through multilevel quantum dots. [1][2][3][4][5][6][7][8] The sequence of tunneling events is correlated by the Coulomb blockade and depends on the effective tunneling rates and internal level structure, which allows for the detection of spin-dependent tunneling through quantum dots. 9 Injection of electrons from spin-polarized leads may result in a spin-dependent blockade as shown by Ciorga et al [10][11][12] The spin blockade effect 13 has been observed in the addition spectrum of a quantum dot in a magnetic field 14,15 as a modulation of the Coulomb blockade peak amplitude or in the occurrence of negative differential resistance.…”
mentioning
confidence: 99%
“…5,6 Zarchin et al 5 found the shot noise to be strongly enhanced in a magnetic field, while the origin of the multilevel system could not be clearly identified. For our system and the magnetic field range presented in Fig.…”
mentioning
confidence: 99%
“…Our motivation are the recent experimental studies 41,42 of shot noise on a quantum point contact, acting as a beam splitter, and those 21 in two capacitatively coupled quantum dots. In the quantum point contact system, the measurements showed an enhancement of shot noise much above the Schottky value 42 and positive current-current cross correlations. 41 Unfortunately, these experiments 41,42 do not give an answer to the origin of bunching of electrons.…”
Section: Introductionmentioning
confidence: 99%